2021
DOI: 10.3390/nu13061821
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal Tongue Pressure Is Associated with Risk of Malnutrition in Community-Dwelling Older Individuals

Abstract: The tongue plays an important role in swallowing, and its dysfunction theoretically leads to inadequate oral intake and subsequent malnutrition. This study aimed to explore how different levels of tongue pressure are related to malnutrition among community-dwelling older individuals. The target population was community-dwelling adults aged ≥ 65 years. Tongue pressure was measured using the Iowa Oral Performance Instrument, whereas the mini nutrition assessment (MNA) test was administered to determine the nutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 33 publications
1
28
0
Order By: Relevance
“…A recent meta-analysis incorporating ten studies also confirmed the significant association between declined MTP and sarcopenia [58]. Chang et al [57] in 2021. A recent meta-analysis incorporating ten studies also confirmed the significant association between declined MTP and sarcopenia [58].…”
Section: Maximal Isometric Tongue Pressurementioning
confidence: 81%
See 1 more Smart Citation
“…A recent meta-analysis incorporating ten studies also confirmed the significant association between declined MTP and sarcopenia [58]. Chang et al [57] in 2021. A recent meta-analysis incorporating ten studies also confirmed the significant association between declined MTP and sarcopenia [58].…”
Section: Maximal Isometric Tongue Pressurementioning
confidence: 81%
“…In 2019, Kobuchi et al [56] assessed 54 elderly residents in a nursing home and found that MTP was positively correlated with grip strength, skeletal muscle mass, and cross-sectional area of the geniohyoid muscle. Furthermore, the association between decreased MTP and malnutrition in community-dwelling elder subjects was identified by Chang et al [57] in 2021. A recent meta-analysis incorporating ten studies also confirmed the significant association between declined MTP and sarcopenia [58].…”
Section: Maximal Isometric Tongue Pressurementioning
confidence: 89%
“…According to a related earlier study, the muscular strength of the anterior tongue improved after oral exercise intervention [ 50 ], supporting the results of this study and verifying the positive effect of oral exercise on tongue pressure in the elderly. A decrease in tongue pressure is one of the oral health problems in the elderly and is deeply correlated with reduced swallowing function and nutritional imbalance, with a potential impact on the physical health of the whole body [ 42 , 51 ]. Thus, oral exercise education is essential in maintaining the basic physical health of the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…During swallowing, the tongue (lower lingual portion) moves the hyoid bone in horizontal and vertical actions; in the pharyngeal phase, the hyoid is pushed forward and upward [45]. Lingual dysfunctions, attributable to advancing age (very frequent) or to the presence of disorders and pathologies, cause dysphagia which decreases the patient's optimal nutrition [47,48]. Another fundamental aspect of the tongue for the model is related to taste.…”
Section: The Metabolic-energy (Nutritional) Model and The Tonguementioning
confidence: 99%